Cerebral Venous Air Embolism Secondary to Mesenteric Infarction - Spanuchart, Ittikorn (Hawaii J Med Public Health, 2016)
Cerebral air embolism is a rare, yet potentially fatal condition. We present a case of retrograde cerebral venous air emboli arising from the hepatic portal venous system, secondary to a mesenteric infarction. A 69-year-old man with a history of gastrointestinal amyloidosis presented with fever and lethargy. Computed tomography of the brain detected multiple foci of air in the right frontal, fronto-parietal, and left lateral frontal sulci consistent with cerebral venous air emboli. Computed tomography of the abdomen and pelvis revealed moderate thickening and dilatation of the small bowel with diffuse scattered intestinal pneumatosis suggestive of mesenteric infarction with resultant extensive intrahepatic portal venous air. The patient was deemed a poor candidate for surgical intervention and died as a result of septic shock. We believe the cerebral venous air emboli was a result of retrograde flow of air arising from the hepatic venous air ascending via the inferior and superior vena cava to the cerebral venous system. To our knowledge, there have been no reported cases of retrograde cerebral venous air embolism arising from hepatic portal venous system secondary to mesenteric infarction. The clinical significance and prognosis in this setting requires further investigation.